How does quality of institutions affect the impact of trade openness on economic growth of Ghana? - Emmanuel Duodu; Samuel Tawiah Baidoo (Cogent Economics & Finance, 2020)
Developing countries, of which Ghana is no exception have actively engaged in trade openness after independence, yet, their economic growth remains low and this calls for urgent attention to address the situation. This study therefore examines the impact of trade openness on economic growth of Ghana for the period 1984-2018 taken into consideration the role quality of institutions play. The results from the autoregressive distributed lag model (ARDL) reveal that, both trade openness and quality of institutions exert a significant positive impact on economic growth in both the long and short run. However, the interaction of trade openness and quality of institutions is shown to have insignificant impact on economic growth in both periods. The results further indicate that exchange rate has a significant positive (significant negative) impact on economic growth in the long run (short run). Based on the findings, the study concludes that, institutional quality has no influence on the impact of trade openness on economic growth in the Ghanaian context. Policy implications aimed at ensuring sustained economic growth have been put forward for the discourse of stakeholders.
Keywords: C22; F10; F43; O40; O43; 330; ARDL; economic growth; Ghana; quality of institutions; trade openness